2007
DOI: 10.1057/palgrave.jibs.8400260
|View full text |Cite
|
Sign up to set email alerts
|

Real options in multinational corporations: organizational challenges and risk implications

Abstract: In this study, we investigate how multinationality affects firms’ risk levels. Our investigation builds on the idea from real options theory that international operations offer switching options to multinational corporations, yet we also emphasize different sources of coordination costs that can mitigate the benefits of operational flexibility. The findings from Tobit models accounting for self-selection underscore the importance of unobserved heterogeneity in the relationships between international investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(181 citation statements)
references
References 67 publications
4
171
2
Order By: Relevance
“…Moreover, the case studies show that (4) systematic training and development of the foreign factories is observed in the case of market-based supply chains and not in the case of internal supply chains. Tong and Reuer (2007) also highlight that the cost of co-ordination increases with the cultural distance between the investor and the foreign affiliate, and show that the performance benefits of multinationality can be offset by the rise in co-ordination costs. One of the case observations illustrates the practice of a supply chain management outpost, i.e.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the case studies show that (4) systematic training and development of the foreign factories is observed in the case of market-based supply chains and not in the case of internal supply chains. Tong and Reuer (2007) also highlight that the cost of co-ordination increases with the cultural distance between the investor and the foreign affiliate, and show that the performance benefits of multinationality can be offset by the rise in co-ordination costs. One of the case observations illustrates the practice of a supply chain management outpost, i.e.…”
Section: Resultsmentioning
confidence: 80%
“…It is only recently that some empirical tests have tried to close this gap. Tong and Reuer (2007), when testing the hypothesized link between multinationality and reduced risk level, contrast the options switching potential of international operations network with the actual cost of co-ordinating the exercise of a switching option. Their conclusion is that the relationship between multinationality and risk levels is not linear.…”
Section: Network Effects and Transaction Costsmentioning
confidence: 99%
“…Finally, resource availability and learning capabilities are crucial for absorbing the full potential of firms' option reserves (Barnett, 2008;Miller, 2002;Miller and Arikan, 2004). As Tong and Reuer (2007) point out, real options reasoning generally leads to increased marginal costs from both greater coordination complexity and greater information load born by managers. For example, the new product development literature posits that staging the innovation process may distance the final product from the original idea if information dependencies are not managed well (Crawford and Di Benedetto, 2008).…”
Section: Resource Availabilitymentioning
confidence: 99%
“…First, certain characteristics of the international network of an MNE, such as its size or presence in a large number of countries, increase its capacity for transferring activities internationally (Allen and Pantzalis, 1996;Tong and Reuer, 2007); the more alternative plants it has in other countries, the easier it will be for it to transfer activities and the more likely it will be that production will be relocated amongst its own plants. Second, when a plant belongs to an international production network, its activity may be transferred without requiring sunk costs, described by Motta and Thisse (1994) as the main barrier to international relocation due to their large proportion over relocation costs.…”
Section: Literature Reviewmentioning
confidence: 99%